Empirical Study on Digital Economy Enabling High-Quality Development of Manufacturing Industry under the New Development Pattern - Wu, Laixin (International Journal of Social Sciences and Public Administration, 2025)
The development of digital economy is leading a profound change in factor allocation and production mode, opening up a favorable time for China’s manufacturing industry to move towards the road of high-quality development. Based on the panel data of the province of China from 2000 to 2024, we analyze how the digital economy empowers the actual effect of high-quality development of the manufacturing industry based on the accurate assessment of the digital economy and the level of high-quality development of the manufacturing industry. The results show that the digital economy and the level of high-quality development of the manufacturing industry have shown significant growth over time, however, this growth is significantly uneven across different regions. The digital economy is significantly driving higher quality in manufacturing. In summary, the digital economy is not only a powerful driver of high-quality development of the manufacturing industry, but its impact also crosses geographical boundaries, revealing the complexity and differences of interregional development.